PENGARUH PELATIHAN KADER TENTANG 5M DAN PENGUKURAN SATURASI OKSIGEN TERHADAP TINGKAT PENGETAHUAN COVID-19 - Pipi Anonyma; Yeni Nur Rahmayanti (Jurnal Infokes, 2023)
Coronavirus disease 2019 (Covid-19) has symptoms of acute respiratory problems such as fever, cough and shortness of breath. The average incubation period is 5-6 days with the longest incubation period being 14 days. The purpose of this study was to find out whether there is an effect of cadre training on 5M and measuring oxygen saturation on the level of knowledge of Covid-19. There were 15 people who said they did not know how to use Oximertry and the normal limits for measuring oxygen saturation. This study used a quantitative descriptive method. This study used a quasi-experimental approach, namely the one group pre-test and post-test approach. The sampling technique used is Simple Random Sampling, namely as many as 40 respondents. Results before Training About 5M and Measuring oxygen saturation mostly with good knowledge of 19 people (47.5%) and after Training About 5M and Measurement of Oxygen Saturation lots of very good knowledge of 21 people (52.5%) with t count is 10.20 and a ρ-value of 0.001 because (p <0.05) it is concluded that there is an effect of Cadre Training on 5M and Oxygen Saturation Measurement on the Knowledge Level of Covid-19.